2013
DOI: 10.1155/2013/521396
|View full text |Cite|
|
Sign up to set email alerts
|

Seroprevalence of Dengue IgG Antibodies among Healthy Adult Population in Lahore, Pakistan

Abstract: Background. Dengue is a mosquito-borne flavivirus infection prevalent in tropical and subtropical regions around the world. Aim of this study was to determine seroprevalence of anti-dengue IgG antibodies in healthy adult population of Lahore and also describe risk factors in relation to dengue seropositivity.Methods. In this cross-sectional study, 274 healthy adult individuals aged 15 years and above were randomly selected using multistage sampling technique. These individuals were interviewed between July–Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…This current study reported a prevalence of 44.4% for dengue-specific IgG antibody among participants, which is in accordance with the findings of Sultana et al,17 who observed 42.9% seroprevalence of anti-dengue IgG in Chittagong, Bangladesh. The seroprevalence from this study is not in conformity with dengue virus-specific IgG seroprevalence of 67.2% by Mahmood et al,18 77% by Adeleke et al,19 79% by Peyerl-Hoffmann et al20 and 98% by Yamashiro et al21 The observed discrepancies in prevalence reports could be due to the level of awareness of dengue, urbanization and environment deterioration 22. The high circulation of dengue virus in the study area could be attributed to several factors including misdiagnosis of febrile cases, the movement of migrants from endemic countries and the proliferation of breeding sites of Aedes mosquitoes 23.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This current study reported a prevalence of 44.4% for dengue-specific IgG antibody among participants, which is in accordance with the findings of Sultana et al,17 who observed 42.9% seroprevalence of anti-dengue IgG in Chittagong, Bangladesh. The seroprevalence from this study is not in conformity with dengue virus-specific IgG seroprevalence of 67.2% by Mahmood et al,18 77% by Adeleke et al,19 79% by Peyerl-Hoffmann et al20 and 98% by Yamashiro et al21 The observed discrepancies in prevalence reports could be due to the level of awareness of dengue, urbanization and environment deterioration 22. The high circulation of dengue virus in the study area could be attributed to several factors including misdiagnosis of febrile cases, the movement of migrants from endemic countries and the proliferation of breeding sites of Aedes mosquitoes 23.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation is in consonance with Bello et al30 and Adeleke et al,19 studies but not with others’ studies18,20,31,32,33 which reported higher prevalence for dengue infection in males than in females. The disparity in the prevalence for gender could be the relatively large number of females recruited for the study compared to fewer males.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, a recent study conducted in Nouméa, New Caledonia, reported the association of higher incidence of dengue rates with lower socioeconomic status 10 . By contrast, various studies conducted in Pakistan found no statistical association between socioeconomic status and dengue seropositivity 11,12 . However, it is significant to mention here that the results of this study cannot be compared with the previous studies, as most studies involve calculation of middle class solely on the basis of accumulative household income, ignoring other factors such as education, wealth, occupation, and lifestyle.…”
mentioning
confidence: 80%
“…The impact of dengue has the potential for severe morbidity in young and healthy individuals, especially in situations of massive outbreaks, as have been happening, for example, in Lahore, Pakistan in 2011, with 500,000 notified cases in a city of 5 million, and a dengue IgG seropositivity rate of 67.9 % the following year in a city not previously endemic for dengue [ 155 ]. Physicians unfamiliar with dengue may at short notice have to deal with critically ill patients either in an outbreak or as a result of travel-related dengue infection [ 156 ].…”
Section: Discussionmentioning
confidence: 99%